A review of the evidence for occupational exposure risks to novel anticancer agents – A focus on monoclonal antibodies. (February 2016) - King, Julie; Alexander, Marliese; Byrne, Jenny; MacMillan, Kent; Mollo, Adele; Kirsa, Sue; Green, Michael
Introduction: Evidence of occupational exposure risks to novel anticancer agents is limited and yet to be formally evaluated from the Australian healthcare perspective. Methods: From March to September 2013 medical databases, organizational policies, drug monographs, and the World Wide Web were searched for evidence relating to occupational exposure to monoclonal antibodies, fusion proteins, gene therapies, and other unclassified novel anticancer agents. Results: Australian legislation, national and international guidelines, and drug company information excluded novel agents or provided inconsistent risk assessments and safe handling recommendations. Monoclonal antibody guidelines reported conflicting information and were often divergent with available evidence and pharmacologic rationale demonstrating minimal internalisation ability and occupational exposure risk. Despite similar physiochemical, pharmacologic, and internalisation properties to monoclonal antibodies, fusion proteins were included in only a minority of guidelines. Clinical directives for the safe handling of gene therapies and live vaccines were limited, where available focusing on prevention against exposure and cross-contamination. Although mechanistically different, novel small molecule agents (proteasome inhibitors), possess similar physiochemical and internalisation properties to traditional cytotoxic agents warranting cytotoxic classification and handling. Conclusion: Novel agents are rapidly emerging into clinical practice, and healthcare personnel have few resources to evaluate risk and provide safety recommendations. Novel agents possess differing physical, molecular and pharmacological profiles compared to traditional cytotoxic anticancer agents. Evaluation of occupational exposure risk should consider both toxicity and internalisation. Evidence-based guidance able to direct safe handling practices for novel anticancer agents across a variety of clinical settings is urgently required.